2017
DOI: 10.1128/msphere.00050-17
|View full text |Cite
|
Sign up to set email alerts
|

Marker Recycling in Candida albicans through CRISPR-Cas9-Induced Marker Excision

Abstract: It is critical to be able to alter genes in order to elucidate their functions. These alterations often rely upon markers that allow selection for a rare cell in a population that has incorporated a piece of DNA. The number of alterations that can be accomplished is thus limited by the number of selection markers that are available. This limitation is circumvented by marker recycling strategies, in which a marker is eliminated after its initial use. Then, the marker can be used again. In this report, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 27 publications
0
58
0
1
Order By: Relevance
“…The approach also requires that both CAS9 and the sgRNA be integrated into the genome, which can be slow and makes sequential editing of several genes difficult. Later, improved versions of CRISPR-Cas9-based genome-editing methods were further developed by exploiting recent observations of C. albicans genetic properties (141)(142)(143)(144)(145)(146). These methods now allow single-or double-gene deletions, tagging, as well as open reading frame (ORF) reconstitutions.…”
Section: Genetic Toolboxmentioning
confidence: 99%
“…The approach also requires that both CAS9 and the sgRNA be integrated into the genome, which can be slow and makes sequential editing of several genes difficult. Later, improved versions of CRISPR-Cas9-based genome-editing methods were further developed by exploiting recent observations of C. albicans genetic properties (141)(142)(143)(144)(145)(146). These methods now allow single-or double-gene deletions, tagging, as well as open reading frame (ORF) reconstitutions.…”
Section: Genetic Toolboxmentioning
confidence: 99%
“…For general growth and propagation, C. albicans strains were grown in yeast extract-peptone-dextrose (YPD) medium (1% yeast extract, 2% peptone, 2% glucose, 2% agar for solid medium) at 30°C. YPD plus 200g/ml nourseothricin (Werner Bioagents, Jena, Germany) was used to select for deletion mutants, and YP maltose (YPM) induced flipping out of the nourseothricin cassette as described previously (69).…”
Section: Strains and Mediamentioning
confidence: 99%
“…albicans. In a follow-up to the Min et al publication, Huang and Mitchell demonstrated a system that enables marker excision in subsequent transformations (8). Briefly, the marker used to delete target gene 1 can be excised during a subsequent transformation that simultaneously integrates a distinct marker in place of target gene 2.…”
Section: Discussionmentioning
confidence: 99%